Supercapacitors: Properties and applications - Libich, Jiří; Máca, Josef; Vondrák, Jiří; Čech, Ondřej; Sedlaříková, Marie (Elsevier, 2018)
Energy accumulation and storage is one of the most important topics in our times. This paper presents the topic of supercapacitors (SC) as energy storage devices. Supercapacitors represent the alternative to common electrochemical batteries, mainly to widely spread lithium-ion batteries. By physical mechanism and operation principle, supercapacitors are closer to batteries than to capacitors. Their properties are somewhere between batteries and capacitors. They are able to quickly accommodate large amounts of energy (smaller than in the case of batteries – lower energy density from weight and volume point of view) and their charging response is slower than in the case of ceramic capacitors. The most common type of supercapacitors is electrical double layer capacitor (EDLC). Other types of supercapacitors are lithium-ion hybrid supercapacitors and pseudo-supercapacitors. The EDLC type is using a dielectric layer on the electrode electrolyte interphase to storage of the energy. It uses an electrostatic mechanism of energy storage. The other two types of supercapacitors operate withelectrochemical redox reactions and the energy is stored in chemical bonds of chemical materials. This paperprovides a brief introduction to the supercapacitor field of knowledge.

Energy accumulation and storage is one of the most important topics in our times. This paper presents the topic of supercapacitors (SC) as energy storage devices. Supercapacitors represent the alternative to common electrochemical batteries, mainly to widely spread lithium-ion batteries. By physical mechanism and operation principle, supercapacitors are closer to batteries than to capacitors. Their properties are somewhere between batteries and capacitors. They are able to quickly accommodate large amounts of energy (smaller than in the case of batteries – lower energy density from weight and volume point of view) and their charging response is slower than in the case of ceramic capacitors. The most common type of supercapacitors is electrical double layer capacitor (EDLC). Other types of supercapacitors are lithium-ion hybrid supercapacitors and pseudo-supercapacitors. The EDLC type is using a dielectric layer on the electrode electrolyte interphase to storage of the energy. It uses an electrostatic mechanism of energy storage. The other two types of supercapacitors operate withelectrochemical redox reactions and the energy is stored in chemical bonds of chemical materials. This paperprovides a brief introduction to the supercapacitor field of knowledge.
Supercapacitors: Properties and applications
Keywords: Supercapacitor; Energy; Storage; Pseudo-supercapacitor; Hybrid-supercapacitor; Lithium; Supercapacitor; Energy; Storage; Pseudo-supercapacitor; Hybrid-supercapacitor; Lithium